Indoor Air Exposure to Multiple Agricultural Pesticides Potentially Posing the Highest Risk to Young Children - Sithembiso Sifiso Msibi; Chung-Yu Chen; Cheng-Ping Chang; Chiou-Jong Chen; Su-Yin Chiang; Kuen-Yuh Wu (Aerosol and Air Quality Research)
Abstract Pesticides are extensively used to improve crop yield and quality in many African countries where agricultural production is a critical economic activity, including Eswatini (formerly Swaziland) in southern Africa. However, the potential health effects of indoor exposure to agricultural pesticides are deeply concerning, and children are particularly vulnerable. This case study assessed such exposure and its risks by sampling and analyzing the air inside the homes of 15 pesticide applicators and 12 non-applicators in Swazi communities surrounded by nearby (~200 m) sugarcane fields on pesticide spraying days. Applying liquid chromatography with tandem mass spectrometry (LC-MS/MS) to the samples revealed mean ametryn, atrazine, pendimethalin and 2,4-dichlorophenoxyacetic acid (2,4-D) concentrations of 0.75, 0.32, 0.57 and 0.004 µg m−3, respectively, in the applicator households and corresponding values of 0.19, 0.03, 0.04 and 0.003 µg m−3, respectively, in the non-applicator households. Notably, the non-applicator households exhibited pesticide concentrations far exceeding previously published data. Furthermore, we measured significantly higher levels of ametryn and pendimethalin inside the homes of the applicators than those of the non-applicators. Daily inhalation exposure to agricultural pesticides resulted in cumulative hazard index values above 1.0 at the 95th percentile for children 3 years of age and younger in the applicator households. Thus, the take-home pathway, spray drift and household-to-field distance all play crucial roles in determining the pesticide exposure and health risks indoors. Owing to the dominance of the first factor, we advise applicators to shower and change into clean clothes before returning home to their families. This safety measure is essential for the many families living near agricultural land throughout Africa.